2016
DOI: 10.5935/1518-0557.20160007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age on blastocyst scoring after single and double embryo transfers

Abstract: Objective: The aim of the present study was to assess the putative relationship between patient's age and blastocyst scores, in single (SET) or double (DET) transfer cycles, that resulted in single or twin pregnancy or non-pregnancy. Second, we analyzed the effect of maternal age on clinical gestation and implantation rates after single and double blastocyst transfers. Methods: Retrospective analysis of 164 assisted reproduction cycles with embryo transfers. Results: Data demonstrated that for both, young (<35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Expansion rate can be measured by the degree of expansion observed on a specific day of culture or by the day of culture on which a blastocyst reaches a sufficient degree of expansion required for vitrification or biopsy. Many studies have shown an impact of morphology and expansion rate of unbiopsied blastocysts on pregnancy rates (Ahlstrom et al, 2013;Ahlström et al, 2011;Awadalla et al, 2020a;Bos-Mikich et al, 2016;Desai et al, 2016;Hill et al, 2013;Honnma et al, 2012;Subira et al, 2016;Thompson et al, 2013;Van Den Abbeel et al, 2013). More information is needed to determine if morphology and expansion rate are still associated with pregnancy after euploid embryos have been selected for transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Expansion rate can be measured by the degree of expansion observed on a specific day of culture or by the day of culture on which a blastocyst reaches a sufficient degree of expansion required for vitrification or biopsy. Many studies have shown an impact of morphology and expansion rate of unbiopsied blastocysts on pregnancy rates (Ahlstrom et al, 2013;Ahlström et al, 2011;Awadalla et al, 2020a;Bos-Mikich et al, 2016;Desai et al, 2016;Hill et al, 2013;Honnma et al, 2012;Subira et al, 2016;Thompson et al, 2013;Van Den Abbeel et al, 2013). More information is needed to determine if morphology and expansion rate are still associated with pregnancy after euploid embryos have been selected for transfer.…”
Section: Introductionmentioning
confidence: 99%